The effect of different methods of cooperative learning model on academic achievement in physics - Okur Akçay, Nilüfer; Doymuş, Kemal (Journal of Turkish Science Education, 2014)
The aim of this study is to determine the effect of group investigation, learning together and readingwriting- presenting methods on students’ academic achievements in teaching of the first year university students attending the classes in which the units of force and motion taught within the general physics course. The sample of this study consists of 121 undergraduates pre-service science teachers during the 2011-2012 academic years in Ağrı İbrahim Çeçen University. As the data collection instruments, Graphic Test (GT), Academic Achievement Test (AAT) and Module Tests (Module A, Module B, Module C, Module D and Module E) were used. This study was carried out in four different groups. One of these groups was Group Investigation Group (GIG), the second group was Learning Together Group (LTG), the third group was Reading-Writing-Presenting Group (RWPG) and the other one was Control Group (CG) in which teacher-centered instruction was applied. The data obtained on instruments were evaluated by using ANOVA and descriptive statistics. The results of this study indicate that teaching of force and motion subjects in RWPG was more effective than the other groups.
Keywords: Group Investigation; Learning Together; Reading-Writing-Presenting; Force and Motion; Physics